2009
DOI: 10.1039/b823406j
|View full text |Cite
|
Sign up to set email alerts
|

Dimerisation of nitrile oxides: a quantum-chemical study

Abstract: The [3 + 2] and [3 + 3] cyclodimerisation processes of small nitrile oxides, XCNO (X = F, Cl, Br, CN, CH(3)) are investigated by ab initio coupled cluster theory at the CCSD, CCSD(T) and MR-AQCC levels for the first time. The favoured dimerisation process is a multi-step reaction to furoxans (1,2,5-oxadiazole-2-oxides) involving dinitrosoalkene-like intermediates with diradical character. The rate determining step for all but the F-species is the first, corresponding to the C-C bond formation. The kinetic ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…This gradient-corrected hybrid functional is well known for the proper reproduction of molecular geometries and vibrational frequencies [34]. A comparison with experimental data for furoxan supports these findings [35]. Therefore, in this work, zero-point vibrational energies were calculated at this level.…”
Section: Methodsmentioning
confidence: 73%
“…This gradient-corrected hybrid functional is well known for the proper reproduction of molecular geometries and vibrational frequencies [34]. A comparison with experimental data for furoxan supports these findings [35]. Therefore, in this work, zero-point vibrational energies were calculated at this level.…”
Section: Methodsmentioning
confidence: 73%
“…The (U)B3LYP method includes measurements of nondynamical and dynamical electron correlation, and it has been shown to provide a good description of geometries for singlet diradical species in cyclization reactions. [8][9][10][11] Our calculations have indicated that a small (2,2) active space is sufficient to describe the two basic configurations in MR-AQCC calculations. It is important to note that the MR-AQCC(2,2)//UB3LYP method provides a reliable and computationally feasible route to calculate the energetics of nitrile oxide dimerisation, as reported.…”
Section: Resultsmentioning
confidence: 89%
“…It is important to note that the MR-AQCC(2,2)//UB3LYP method provides a reliable and computationally feasible route to calculate the energetics of nitrile oxide dimerisation, as reported. [9] The previous work also included tests involving a larger active space and various basis sets. Therefore, MR-AQCC (2,2)//(U)B3LYP/cc-pVTZ calculations were performed for investigating bimolecular reactions; energies of closed-shell singlet reacting species, namely, nitrile selenides, nitriles, ethenes, and ethynes, were calculated at the SR-AQCC// B3LYP/cc-pVTZ level.…”
Section: Resultsmentioning
confidence: 99%
“…So it is necessary to remove the spin contamination. Previous investigations indicated that using (U)DFT with the hybrid B3LYP functional method can provide a good description of the geometry of cyclization reactions, in particular those that involve singlet diradical species . The CASSCF single‐point energy calculations based on (U)B3LYP‐optimized geometries have been performed to investigate the dimerization reaction mechanism of nitrile oxides .…”
Section: Resultsmentioning
confidence: 99%